2020
DOI: 10.1186/s13568-020-01053-z
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane alter the microbiota and mitigate colitis severity on mice ulcerative colitis induced by DSS

Abstract: Sulforaphane (SFN) is a kind of natural isothiocyanate, which exists in cruciferous plants. Only few studies were about the anti-inflammatory effects of sulforaphane in ulcerative colitis. In this study, our purpose is to explore the effects of sulforaphane on the intestinal microbial community of UC mice. The severity of mice colitis were measured by colon length, survial rate, body weight and disease activity index (DAI) score. Histological and morphological evaluation of colon tissues were performed by HE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…It was also observed that Gln increased the Firmicutes / Bacteroidetes ratio, decreased the abundance of Firmicutes , and beneficially changed the bacterial community and activated the innate immunity in the intestine [ 52 ]. It was reported that the decrease in Bacteroides and the increase in Firmicutes have a defensive effect on IBD [ 53 ]. The abundance of Firmicutes in DSS-induced colitic mice was also increased by serine [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that Gln increased the Firmicutes / Bacteroidetes ratio, decreased the abundance of Firmicutes , and beneficially changed the bacterial community and activated the innate immunity in the intestine [ 52 ]. It was reported that the decrease in Bacteroides and the increase in Firmicutes have a defensive effect on IBD [ 53 ]. The abundance of Firmicutes in DSS-induced colitic mice was also increased by serine [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased in Parkinson's disease (259) Increased in autism spectrum disorder (256,257) Correlated with levels of serotonin (303) Prevotellaceae Decreased in IBS (248) Increased in IBS (304) Increased in IBD (326) Increased in UC and CD (252) Decreased in Parkinson's disease (254,327) Decreased in autism spectrum disorder (256,321) Proteobacteria Enterobacteriaceae Increased in IBS (302) Increased in IBD (292,306) Increased in UC and CD (252) Increased in Parkinson's disease (328) Increased in Alzheimer's disease (300) Increased in autism spectrum disorder (257) Decreases 5-HT and SERT protein (329) Increase 5-HT bioavailability (330) Increases EC cells (331) Serotonin-producing bacterial strains (Escherichia coli K-12) insufficient, and novel studies have indicated that more treatments addressing innate immunity should be carried out. In this context, several studies have indicated that TLR (353) and NLR (354) modulation may help in the treatment of these chronic pathologies.…”
Section: Ruminococcaceaementioning
confidence: 99%
“…In memoriam: This paper is dedicated to the memory of Professor Ana Isabel Alcalde, a brilliant and enthusiastic Verrucomicrobia Akkermansiaceae Reduced in IBD (297,311) Reduced in UC (342) Increased in Parkinson's disease (254,255,327) Increased in autism spectrum disorder (256) Increases SERT expression (296) Increases 5-HT in colon and hippocampus (8) Akkermansia are decreased in SERT -/mouse (262)…”
Section: Author's Notementioning
confidence: 99%
“…To identify the PAMPs or DAMPs, the NLR family member, NLRP3, plays an important role. Additionally, as a major component of innate immunity, the NLRP3 inflammasome plays a critical role in the inflammatory response, providing a molecular platform that can be triggered by multiple endogenous and exogenous stimuli including ATP, microbial agonists, particulate matter, and pore-forming toxins [ 22 , 23 ]. The NLRP3 inflammasome multiprotein complex consists of the NLRP3 sensor, the speck-like adaptor-apoptosis-associated protein containing a domain of caspase recruitment (ASC), and the effector protein caspase-1.…”
Section: Discussionmentioning
confidence: 99%